Gender norms and farming households in rural Rwanda: a GENNOVATE case-study for the Nyamirama sector in Kayonza district - Rietveld, Anne M. (International Potato Center, 2018)
This report presents data and results from a GENNOVATE case-study conducted in the Nyamirama sector in Kayonza district in Rwanda that focusses on gender norms and agency in relation to agricultural innovation.